Community Empowerment Through Assistance in The Creation of Business Identification Numbers in Laweyan Village - Astuti, Titiek Puji; Wulandari, Rosi; Hidayati, Nur (Indonesian Journal of Devotion and Empowerment, 2024)
Micro, small and medium enterprises (MSMEs) are increasingly mushrooming and developing, especially in Laweyan Village, where Laweyan Village is one of the centers of batik craftsmen in Surakarta City and not a few make Laweyan Village a tourist spot or a place for comparative studies for other MSMEs. The increasing number of tourists coming to Laweyan Village has resulted in newer MSMEs. This cause had a positive impact on the economy of the people in Laweyan village. However, new problems will arise such as business owners not having business identification numbers (NIB). Therefore, the community service team has carried out socialization and direct services for making NIB through online single submission (OSS) to micro, small, and medium enterprises. The methods applied include: approach methods, tutorials, discussion group forums, comprehensive, learning by doing, and technological methods. Business owners will be given knowledge about the importance of NIB and accompanied in the NIB registration until getting it. The activity was attended by businessmen and sororities. Starting from socialization to assistance in making the NIB. It is provided from the start of registration until the NIB is issued. From this activity, 3 NIBs were successfully issued.